2017
DOI: 10.1108/ilt-12-2015-0201
|View full text |Cite
|
Sign up to set email alerts
|

Friction characteristics of hybrid magnesium alloy composites reinforced with carbon nanotube and cerium

Abstract: Purpose The paper aims to clarify the hybrid Mg alloy composites reinforced with multi-walled carbon nanotube (MWCNT) and Cerium (Ce) rare earth element tribological properties were investigated by using pin-on-disk test configuration under dry and lubricated sliding conditions. Design/methodology/approach The paper opted for an experimental study with composite samples under lubricated conditions. Their tribological properties were investigated by using pin-on-disk test configuration under dry and lubricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The hardness of a processed composite specimen was investigated using Vickers' micro hardness tester. The wear test was conducted using pinon-disc friction and wear testing machine, which is simple, accurate and widely used by many researchers (Ayyappadas et al, 2017;Mojumder et al, 2017;Mat Tahir et al, 2017;Sari et al, 2017;Gladston et al, 2017). In total, 12 samples were prepared from the processed composite, and the dimensions were 4 Â 4 Â 50 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The hardness of a processed composite specimen was investigated using Vickers' micro hardness tester. The wear test was conducted using pinon-disc friction and wear testing machine, which is simple, accurate and widely used by many researchers (Ayyappadas et al, 2017;Mojumder et al, 2017;Mat Tahir et al, 2017;Sari et al, 2017;Gladston et al, 2017). In total, 12 samples were prepared from the processed composite, and the dimensions were 4 Â 4 Â 50 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 6 (a) shows the EDS analysis of the worn surface of RZ5/4 wt.% TiB 2 magnesium matrix composites for an applied load of 10 N and a sliding distance of 2000 m. The EDS analysis indicates the elements of magnesium RZ5 alloy (Mg-Zn-Zr-RE) and TiB 2 along with some oxide peaks. In the EDS analysis of wear debris shown in Figure 6 (b), it can be observed that wear debris got oxidized during the wear test, and the size of the wear debris formed is around (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) µm.…”
Section: Micrograph Of Worn Surface and Wear Debrismentioning
confidence: 99%
“…Different wear mechanisms were observed at different sliding speeds during wear, and at the lower sliding speed, the oxide layer was deposited on the contact surface and protected from wear. 15 Many researchers have investigated the tribological behaviour of different alloys and their composites experimentally with varying wear parameters. However, it is challenging to perform the experiments at all operating conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium alloys are promising structural materials in many industrial applications (Sari et al , 2017). One of the major advantages for today’s technology is that magnesium can be easily recycled (Huang et al , 2006).…”
Section: Introductionmentioning
confidence: 99%